The Effectiveness of Online Learning: The Implementation of Hand Hygiene as a COVID-19 Prevention of the Cognitive and Affective Capabilities of Nursing Students - Safitri, Alfia; Yuliana, Nila; Alfian, Alfian; Taradipa, Egi; Aryani, Awalia Septi (Indonesian Publication Center, 2020)
The capability of the nursing student to apply hand hygiene in COVID-19 prevention is important. Online learning is a solution to the effective learning method if face to face learning is not being done. This study aims to evaluate the effectiveness of online learning about hand hygiene application as COVID-19 prevention to improve cognitive and affective abilities in Nursing students. This is a pre-Experimental design with one group pre-posttest involved 37 students. The study was conducted in April 2020 by providing health education with handouts, modules, and video hand hygiene according to the World Health Organization (WHO) guidelines. The intervention carried out three days through google classroom. Pre and post-intervention measurements were taken to assess respondents' cognitive and affective abilities with a questionnaire. The statistical analysis used for cognitive and affective abilities was the Wilcoxon Signed Rank Test. The result of the study found that there were no significant changes in respondents' cognitive ability with P-Value 1.000 (P> 0.05) and affective ability P-Value 0.165 (P> 0.05) for pre and post hand hygiene online learning using google classroom. Further studies are needed to use other methods and innovative learning media to improve students' abilities in the application of hand hygiene.